Absence of RIPK3 predicts necroptosis resistance in malignant melanoma - Geserick, Peter (Cell death & disease, 2015)
Acquired or intrinsic resistance to apoptotic and necroptotic stimuli is considered a major hindrance of therapeutic success in malignant melanoma. Inhibitor of apoptosis proteins (IAPs) are important regulators of apoptotic and necroptotic cell death mediated by numerous cell death signalling platforms. In this report we investigated the impact of IAPs for cell death regulation in malignant melanoma. Suppression of IAPs strongly sensitized a panel of melanoma cells to death ligand-induced cell death, which, surprisingly, was largely mediated by apoptosis, as it was completely rescued by addition of caspase inhibitors. Interestingly, the absence of necroptosis signalling correlated with a lack of receptor-interacting protein kinase-3 (RIPK3) mRNA and protein expression in all cell lines, whereas primary melanocytes and cultured nevus cells strongly expressed RIPK3. Reconstitution of RIPK3, but not a RIPK3-kinase dead mutant in a set of melanoma cell lines overcame CD95L/IAP antagonist-induced necroptosis resistance independent of autocrine tumour necrosis factor secretion. Using specific inhibitors, functional studies revealed that RIPK3-mediated mixed-lineage kinase domain-like protein (MLKL) phosphorylation and necroptosis induction critically required receptor-interacting protein kinase-1 signalling. Furthermore, the inhibitor of mutant BRAF Dabrafenib, but not Vemurafenib, inhibited necroptosis in melanoma cells whenever RIPK3 is present. Our data suggest that loss of RIPK3 in melanoma and selective inhibition of the RIPK3/MLKL axis by BRAF inhibitor Dabrafenib, but not Vemurafenib, is critical to protect from necroptosis. Strategies that allow RIPK3 expression may allow unmasking the necroptotic signalling machinery in melanoma and points to reactivation of this pathway as a treatment option for metastatic melanoma.
Gesehen am 28.02.2018